FY2018 Benin Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2019)
The Country Opinion Survey in Benin assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Benin perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Benin on 1) their views regarding the general environment in Benin; 2) their overall attitudes toward the WBG in Benin; 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Benin; and 4) their perceptions of the WBG’s future role in Benin.